Association of Estrogen and Progesterone with Ovarian Cancers - Asma Qamar Mudassir, Arifa Zafar, Uzma Zia, Rukhsana Saboor, Tayyaba Rasheed, Shabana Bano Soomro (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find an association between estrogen and progesterone with ovarian cancer progression. Study Design: Cross-sectional study Place and Duration of Study: Department of Obstetrics & Gynaecology, Islam Teaching Hospital, Sialkot from 1st January 2021 to 31st December 2021. Methodology: One hundred participants were enrolled. Ovarian cancer women were placed in Group A while healthy woman in Group B. The study was approved from the review board. The age of the patients was between 18-45 years. Demographic details as well as clinical and relevant familial history was documented of each patient. The blood sampling was done on same menstrual day 12 in each patient. Each patient 4 cc blood was withdrawn for analysis if their estrogen and progesterone levels. The blood was collected in serum vials and serum was separated by centrifugation at 3000rpm. The patients who were confirmed for ovarian cancer CA 125 were confirmed through clinical diagnosis in addition to their MRI and CT scan imaging. Results: The mean age of the patients was 33.3±2.1 years of ovarian cancers while 21.5±3.4 years of normal controls. Majority of the females were from low socioeconomic class. The values of progesterone and estrogen were significantly higher in CA 125 cases such as Group A in comparison with group B respectively. The analytes were assessed in the follicular phase and showed higher frequency in 96% and 94% of cases with ovarian cancer. The mean value was 2±0.4ng/ml and 119.1±2.9 pg/ml respectively. Conclusion: In ovarian cancer, level of estrogen was very higher during follicular phase. Keywords: Ovarian cancer, Advanced epithelial cancer, Estrogen, Progesterone, Abnormal secretion